2016
DOI: 10.21860/medflum2016_4ser
|View full text |Cite
|
Sign up to set email alerts
|

Type 1 diabetes mellitus in children

Abstract: Sažetak. Šećerna bolest tipa 1 (ŠB) najčešća je endokrinološka bolest dječje dobi. Karakterizirana je deficitom inzulina koji nastaje zbog autoimunog uništenja β stanica gušterače. Javlja se u genetski predisponiranih osoba, a može biti potaknuta provocirajućim čimbenicima iz okoliša. Incidencija ŠB-a tipa 1 u djece je u porastu, u prvom redu u djece mlađe od 5 godina. Znakovi i simptomi bolesti razvijaju se brzo, obično u periodu kroz nekoliko tjedana. Tipični simptomi su poliurija, polidipsija, polifagija i … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 59 publications
2
1
0
Order By: Relevance
“…Uncontrolled diabetes increases the risk of development of microangiopathy and related complications or sequelae. Our study showed that a higher percentage (64.0%) of patients with cutaneous manifestation had systemic complications, like peripheral neuropathy, hypertension, retinopathy, nephropathy, coronary artery disease and cerebrovascular disease ,as was reported by Shemeret et al [26] , Bhat et al [4] and Mahajan et al [6] 55.5%, 87%, 89% respectively. Neuropathy was the most common complications (35.0%) documented in our study.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Uncontrolled diabetes increases the risk of development of microangiopathy and related complications or sequelae. Our study showed that a higher percentage (64.0%) of patients with cutaneous manifestation had systemic complications, like peripheral neuropathy, hypertension, retinopathy, nephropathy, coronary artery disease and cerebrovascular disease ,as was reported by Shemeret et al [26] , Bhat et al [4] and Mahajan et al [6] 55.5%, 87%, 89% respectively. Neuropathy was the most common complications (35.0%) documented in our study.…”
Section: Discussionsupporting
confidence: 83%
“…The complications of diabetes mellitus are many and inter-related and are mostly a result of poor glycemic control, hypertension, hyperlipidemia, obesity, and smoking [11] . There has been no significant statistical association between diabetic dermoangiopathy and diabetic retinopathy, neuropathy, nephropathy, or hypertension (P>0.05) in our study and similar results have been obtained by Mahajan et al [6]. In our study, type II DM has been associated with increased risk of diabetic complications, compared to type 1 DM, although the increased frequency had not achieved statistical significance.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation